EFEKTIVITAS MODEL PEMBELAJARAN PEROLEHAN KONSEP (CONCEPT ATTAINMENT) TERHADAP KEMAMPUAN MENEMUKAN UNSUR-UNSUR INTRINSIK CERPEN “KISAH DI KANTOR POS” KARYA MUHAMMAD ALI OLEH SISWA KELAS IX SMP N 4 TARUTUNG TAHUN PEMBELAJARAN 2012/2013 - Fitria Hutagalung (Universitas Negeri Medan, 2012)
This research aims to determine the effectivity of concept attainment model in learning to discover short stories’ intrinsic elements of the ninth grade students of SMP N 4 Tarutung, in academic year 2012/2013. The population of this research was as many as 120. The sample was taken randomly as many as 40 students, 20 students for experimental class and 20 other students for control class. The method of this research was the experimental method. The instrument conducted was to discover intrinsic elements of short stories in post-test form. The average of the experimental class was 75.25, while the average of control class was 65.25. Hence, it can be said that the score in finding intrinsic elements of experimental class was higher than contol class’ score. Hypothesis testing was conducted by using , from the calculation of hypothesis testing, it was found that the score of was 4.61, furthermore it was consultated by table with significan level 5% = 1.68 and in level 1% = 2.42, with df level = (20+20) – 2 = 38. In table t with df level = 38, it was found that in significan level the hypothesis was effective, because <> namely, (1.68<4.61>2.42) thus, the alternative hypothesis (Ha) was accepted. Therefore, it is concluded that concept attainment model in learning was effectively used in finding intinsic elements of short stories by the ninth grade of SMP N 4 Tarutung, academic year 2012/2013. Keywords: effectivity, concept attaiment model, intrinsic elements,